2023
DOI: 10.1007/s40279-023-01853-w
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Demands of Repeated-Sprint Training on Physiological, Neuromuscular, Perceptual and Performance Outcomes in Team Sport Athletes: A Systematic Review and Meta-analysis

Abstract: Background Repeated-sprint training (RST) involves maximal-effort, short-duration sprints (≤ 10 s) interspersed with brief recovery periods (≤ 60 s). Knowledge about the acute demands of RST and the influence of programming variables has implications for training prescription. Objectives To investigate the physiological, neuromuscular, perceptual and performance demands of RST, while also examining the moderating effects of programming variables (sprint mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 293 publications
0
2
0
Order By: Relevance
“…Moreover, the lowest division in our study (4th league) was from the first national league which differs from a regional championship. Contrary to our protocol, the Bangsbo RSA includes a change of direction component and it has been shown that shuttle-type RSA protocols are associated with slower repetition times and a reduced sprint decrement ( Thurlow et al, 2023 ).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the lowest division in our study (4th league) was from the first national league which differs from a regional championship. Contrary to our protocol, the Bangsbo RSA includes a change of direction component and it has been shown that shuttle-type RSA protocols are associated with slower repetition times and a reduced sprint decrement ( Thurlow et al, 2023 ).…”
Section: Discussionmentioning
confidence: 90%
“…Long rest periods between repetitions were selected to reduce intra-session fatigue and maintain the maximum intensity in each 40-m repetition. The designed protocol is further supported by the findings of a recent systematic review and meta-analysis on the demands of RST in team sports ( Thurlow et al, 2023 ), which include that (i) a distance of 40 m (or 6-s sprints), commonly used in team sports, allows the maximum velocity to be reached; and (ii) longer rest intervals are recommended in order to maintain the quality of the repetitions when the total volume is greater. Then, blood samples were collected to determine changes in serum biomarkers, and muscle function was assessed by posterior chain FGC, lower limbs ROM and sprint performance and mechanical properties test.…”
Section: Methodsmentioning
confidence: 99%
“…The range of the loads considered very heavy resistance (>30% velocity decrement) in the classification of resisted sprint loads [65]. We chose to use 30% Vdec loads in this study, given that the athletes may have relatively low levels of muscular strength and would need to perform sprints repeatedly after a short 40 s rest period [13,18,39]. The loads of 30% Vdec for the participants was an average value of 10.9 ± 0.79 kg.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…Soccer players often perform sprint training with short rest intervals (≤60 s) to improve their ability to perform repeated sprints [13][14][15][16][17][18]. Adaptation to these short rest intervals between sprints can enhance recovery mechanisms and the activity of enzymes involved in both aerobic and anaerobic energy production [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation